2008
DOI: 10.1074/jbc.m707610200
|View full text |Cite
|
Sign up to set email alerts
|

The Mechanism of Cystic Fibrosis Transmembrane Conductance Regulator Transcriptional Repression during the Unfolded Protein Response

Abstract: The unfolded protein response (UPR) aids cellular recovery by increasing the capacity and decreasing the protein load of the endoplasmic reticulum (ER). Although the main pathways of the UPR are known, the mechanisms of UPR-associated transcriptional repression have not been explored in mammalian cells. Previous studies indicate that endogenous cystic fibrosis transmembrane conductance regulator (CFTR) mRNA levels and protein maturation efficiency decrease when the UPR is activated. In the present study, we de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
80
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(83 citation statements)
references
References 84 publications
1
80
0
Order By: Relevance
“…It has been recently shown that ATF6 is responsible for cystic fibrosis transmembrane conductance regulator transcriptional repression by binding to its promoter [48]. Our analysis of the minimal promoter region of Glut4, Mef2a and Pgc1α (GenBank accession numbers: NC_005109.2, NW_001084766.1 and NC_005113.2), using MatInspector, identified several putative binding sites for ATF6 and for other UPR regulatory factors.…”
Section: Discussionmentioning
confidence: 99%
“…It has been recently shown that ATF6 is responsible for cystic fibrosis transmembrane conductance regulator transcriptional repression by binding to its promoter [48]. Our analysis of the minimal promoter region of Glut4, Mef2a and Pgc1α (GenBank accession numbers: NC_005109.2, NW_001084766.1 and NC_005113.2), using MatInspector, identified several putative binding sites for ATF6 and for other UPR regulatory factors.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, a previous study from Bartoszewski and colleagues showed that the repression of the gene coding for the cystic fibrosis transmembrane conductance regulator (CFTR) is maintained during endoplasmatic reticulum stress by recruitment of methyl-binding proteins and/or HDACs. The repressed state of CFTR depends on the binding of MAZ to a hypermethylated region of the promoter, showing methylation-specific repression by MAZ in this case as well (33).…”
Section: Gatamentioning
confidence: 99%
“…Therefore, it is unlikely that CFTR mutations would play a significant role in this study. Alternatively, apart from changes in hormonal levels, DNA methylation and histone deacetylation may contribute to CFTR transcriptional regulation (Rochwerger et al 1994, Bartoszewski et al 2008, which may be altered during aging.…”
Section: Discussionmentioning
confidence: 99%